Fundamentals of Organizing Independent Education in Primary Education in Uzbekistan - Saparbayeva Dinorakhan Turgunboy kizi (Academia One Publishing, 2023)
the article analyzes the national foundations of independent education in the process of primary education in Uzbekistan and presents methodical recommendations
Keywords: Uzbekistan; beginning; education